Vasospasm or Atherosclerotic Lesion of Coronary Arteries: Case Management - V. K. Tashchuk; I. O. Makoviichuk; M. V. Al Salama; O. V. Malinevska-Biliichuk; S. S. Biletskiy; A. A. Lisovenko (Український журнал серцево-судинної хірургії, 2020)
Background. Coronary artery vasospasm (CVS) is an important mechanism of myocardial ischemia which can produce any of the manifestations of coronary artery disease from silent myocardial ischemia to acute coronary syndrome including myocardial infarction or sudden cardiac death. One of the main markers of CVS is retrosternal pain not associated with increased myocardial oxygen requirement such as that due to exercise or emotional excitement with frequent attacks in the morning and temporary ST segment elevation. Some patients have variant angina caused by the spasm of coronary arteries (СА) coupled with stable angina provoked by emotional and physical stress. Such patients have decreased exercise tolerance.